Integrating Aquaculture and Culinary Tourism: Community based development of the Sriharjo culinary centre - Wardiyanta, Wardiyanta; Rahmayanti, Ifada; Pangastuti, Palupi Melati (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
This community service programme was designed to strengthen local economic empowerment in Sriharjo Village through the integration of aquaculture and culinary tourism. Using a community-based participatory approach, the programme engaged the village government, Bumkal Sri Rejeki, the fish farmers’ association (Pokdakan), youth, and women’s groups. Activities included institutional visits, dialogue forums, coordination meetings, culinary competitions, and training on business management and digital promotion. Outcomes were evaluated using a one-group pre-test–post-test quasi-experimental design with questionnaires, observation, and documentation. The results show significant improvements in participants’ competencies. The greatest increase was recorded in product processing knowledge (+70.59%), followed by food processing and content knowledge (+47.06%). Moderate gains were achieved in raw materials management (+29.41%), fish freshness recognition (+29.42%), nutrition knowledge (+18%), and marketing strategies (+29.42%). Social media knowledge also improved (+23.53%), reflecting growing digital engagement. In contrast, paid advertising knowledge increased slightly (+5.89%), while digital marketing knowledge remained unchanged (0%), indicating a strong baseline but limited application. These findings demonstrate that stakeholder collaboration, participatory governance, and experiential training effectively build technical and managerial capacities. However, uneven outcomes across domains emphasise the need for more practice-oriented interventions, particularly in digital and financial literacy, to ensure long-term sustainability of community-based economic initiatives.